Harassment of Women in University and Public Transport - Sumbal, Sumbal (European Scientific Journal, ESJ, 2022)
The present study was conducted to find out the existing problems of university and public transport from the perspective of females in Abdul Wali Khan University Mardan, KP, Pakistan. The study examines the issue of harassment in university and public transport the female faces every day. The study uses the quantitative method and random sampling, which belongs to probability sampling—the data collected from the study area through the questionnaire. The study shows that students and employees were 18 to 31 years old in which majority of the female’s faces problems in public transport and few were faced problems in university transport. The study shows that the female passenger was unwilling to use public transport. They found it the most unattractive mode of transportation. Moreover, the study shows that most females reported facing the misbehaviour of drivers and co-passengers. The female passengers do not want to use public transport to avoid unpleasant situations. They also feel unsafe from drivers because they make rude remarks behind them, harass them, and miss their behaviour. Most of them want to act against the harassers, but they are afraid, and those who are harassed do not complain to the higher authorities because they think it can affect their selfrespect and reputation. Further studies need to be conducted to get more information about public and university transport harassment.